2019
DOI: 10.1111/apt.15441
|View full text |Cite
|
Sign up to set email alerts
|

Risk of rebleeding, vascular events and death after gastrointestinal bleeding in anticoagulant and/or antiplatelet users

Abstract: Summary Background Patients with gastrointestinal bleeding during anticoagulant and/or antiplatelet therapy represent a clinical challenge. Aim To determine the risk/rates of rebleeding, vascular events and death in patients treated with antiplatelet or anticoagulant agents who developed major gastrointestinal bleeding Methods This was an observational cohort study of patients who developed gastrointestinal bleeding while on antiplatelet and/or anticoagulant therapy. Drug use information was collected prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…Our study provides information about the location and the etiology of gastrointestinal bleeding. More patients had lower than upper gastrointestinal bleeding, in agreement with findings from our previous studies analyzing gastrointestinal bleeding events in patients taking DAPT [8] and antiplatelets in general [29]. In fact, currently, there are more hospital admissions of patients presenting with lower than with upper gastrointestinal bleeding [33], which can be explained in part by the large number of patients receiving concomitant treatment with PPI [8].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study provides information about the location and the etiology of gastrointestinal bleeding. More patients had lower than upper gastrointestinal bleeding, in agreement with findings from our previous studies analyzing gastrointestinal bleeding events in patients taking DAPT [8] and antiplatelets in general [29]. In fact, currently, there are more hospital admissions of patients presenting with lower than with upper gastrointestinal bleeding [33], which can be explained in part by the large number of patients receiving concomitant treatment with PPI [8].…”
Section: Discussionsupporting
confidence: 89%
“…The paradoxical outcome is that these new antiplatelets are not used in patients with higher cardiovascular risk and who might benefit the most. Additionally, the management of DAPT in patients with gastrointestinal bleeding is a challenge in clinical practice because recent evidence suggests a benefit from the early resumption of antiplatelet therapy [29]. Given this lack of conclusive findings, we conducted a study to determine the risk for specific types of major and minor gastrointestinal events in patients taking DAPT, depending on the type of treatment used.…”
Section: Introductionmentioning
confidence: 99%
“…bleeding, it was recommended that in patients with peptic ulcer hemorrhage, antithrombotic agents could be restarted the same day or not be interrupted at all if endoscopy demonstrates a Forrest III (clean base) ulcer [33]. A recent retrospective cohort study, including 871 GI bleeding patients, of whom 25 % had peptic ulcer hemorrhage and all of whom were taking antithrombotic medications (52.5 % antiplatelet agents), showed that at long-term follow-up (mean 24.9 months), resumption of either antiplatelet or anticoagulant therapy was associated with a higher risk of rebleeding, but a lower risk of an ischemic event or death [34]. Moreover, the investigators reported that when compared to late resumption of antithrombotic therapy, early resumption (≤ 7 days) following the bleeding episode showed no difference in mortality, a lower rate of ischemic events (13.6 % vs. 20.4 %), yet a significantly higher rate of GI rebleeding (30.6 % vs. 23.1 %; P = 0.04).…”
Section: Recommendationmentioning
confidence: 99%
“…Згідно зі світовою статистикою [5], майже 5-7% населення планети, серед яких частка людей похилого вік сягає 40-60%, постійно приймають НПЗП, застосування яких пов'язане з цілим рядом побічних явищ і ризиків, серед яких лідером є ураження слизової оболонки шлунково-кишкового тракту (ШКТ) від стравоходу до прямої кишки. Однак частота ушкодження гастродуоденальної зони (ГДЗ) розвивається приблизно в 6 разів частіше, що обґрунтовує актуальність проблеми гастробезпеки при застосуванні неселективних НПЗП, прийом яких асоціюється із розвитком НПЗП-гастропатії та підвищеним ризиком кровотеч і перфорацій ШКТ [1][2][3][4].…”
Section: вступunclassified